Interpreting terminology/ Terminologie van het tolken/ Tolkterminologie/ Mareo a botoloki/ Amatemu okutolika - Pienaar, Marné (African Sun Media, 2018)
This dictionary of interpreting terminology is aimed at people who are being trained as interpreters, interpreter trainers, people who work as interpreters, or scholars who engage in research in the field of interpreting and who are looking for interpreting terms, either in English, Dutch, Afrikaans, Northern Sotho or Zulu. The localisation and translation of the dictionary were guided by the interpreting context in South Africa, which so often differs markedly from contexts in other countries.